Effect of resin content and density on the properties three layer particleboard from kelempayan (neolamarckia cadamba) and wood shaving / Abdul Halim Mohd Hatta and Jamaludin Kasim - Mohd Hatta, Abdul Halim; Kasim, Jamaludin (2015)
Particleboard is a composite panel product consisting of cellulosic particle of various sizes that are bonded together with a synthetic resin or binder under pressure and heal. The species of Kelempayan (Neolamarckia cadamba) with diameter 40 cm at breast height 25m height, from 1 log diameter was converted into particle by using scale knife ring flaker. The target densities were 500 kg/m3, 600 kg/m3 and 700 kg/m3. The particle that was used in this process is unscreened and was dried to certain moisture contain. The particleboard was produced in different densities and resin contents; 8%, 10% and 12% with addition 1% of wax using adhesive urea formaldehyde (UF). This research is to determine the physical and mechanical properties of particleboard and effects of resin contents and density on Kelempayan and shavings on' particleboard properties. The particleboard testing followed JIS Standard to determine the physical properties. Collected data was analysed by using Microsoft Excel and Statistical Packages for the Social Science (SPSS). From the result, Wood ratio showed significant effect to all board properties. Whereas for resin content, there were significant impact on MOR, TS and WA.